2004
DOI: 10.1152/ajplung.00120.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fas/FasL-mediated apoptosis in perinatal murine lungs

Abstract: I. Luks. Fas/FasL-mediated apoptosis in perinatal murine lungs. Am J Physiol Lung Cell Mol Physiol 287: L730 -L742, 2004; 10.1152/ajplung.00120.2004.-Postcanalicular lung development is characterized by a time-specific increase in alveolar epithelial type II cell apoptosis. We have previously demonstrated that, in fetal rabbits, developmental type II cell apoptosis coincides with transient upregulation of the cell death regulator Fas ligand (FasL). The aims of this study were 1) to determine the spatiotemporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…10 Briefly, type II cells were isolated by protease digestion and differential adherence to CD45-and CD32-coated dishes. After isolation and purification, the cells were resuspended in culture medium (HEPESbuffered Dulbecco's modified Eagle's medium, 10% fetal bovine serum, 100 U/ml penicillin, 100 g/ml streptomycin).…”
Section: Alveolar Type II Cell Isolation and Culturementioning
confidence: 99%
See 4 more Smart Citations
“…10 Briefly, type II cells were isolated by protease digestion and differential adherence to CD45-and CD32-coated dishes. After isolation and purification, the cells were resuspended in culture medium (HEPESbuffered Dulbecco's modified Eagle's medium, 10% fetal bovine serum, 100 U/ml penicillin, 100 g/ml streptomycin).…”
Section: Alveolar Type II Cell Isolation and Culturementioning
confidence: 99%
“…First, we previously demonstrated that perinatal murine respiratory epithelial cells are exquisitely sensitive to Fasmediated apoptosis in vitro and in vivo. 10,22 Furthermore, the Fas/FasL signaling pathway lends itself better to experimental manipulation than other, in particular intrinsic (mitochondrial-dependent) pathways. Finally, the Fas/ FasL system has been implicated as critical regulator of alveolar type II cell apoptosis in physiological alveolar remodeling 10,11 and in various clinical and experimental models of adult lung injury.…”
mentioning
confidence: 99%
See 3 more Smart Citations